The impact of artificial intelligence on the labour market: Evidence from China - Ruitao Li; Chuanxian Li; Shijun Guo (Amfiteatru Economic, 2024)
The rapid advancement of artificial intelligence (AI) technology has been the driving force behind the new wave of technological revolution. In this study, we examine the impact of AI technology on corporate employment decisions. Using a sample of Chinese listed firms from 2012 to 2021, we find that AI technology applications have a positive influence on the total number of corporate employees. In addition, we find that this positive relationship is more pronounced in non-state-owned enterprises and in asset-light companies. Furthermore, our mechanism analysis indicates that AI technology has positive effects on corporate employment by increasing sales revenue and attenuating financial constraints. In general, our findings highlight the importance of AI technology to the labour market and have several implications for corporate employment decisions.
Keywords: O3; G3; J0; 330; Artificial intelligence; employees; labour market; patents